Process Writing and Enhancement of Critical Thinking Ability: Is Writing a Vehicle or an Ingredient of Critical Thinking? - Reihaneh Sheikhy Behdani; Mojgan Rashtchi (Iranian Journal of Applied Language Studies, 2019)
The study aimed to investigate the relationship between process writing (PW) and critical thinking (CT) ability of Iranian EFL learners. Furthermore, the role of PW in the enhancement of CT was investigated. In so doing, 65 upper-intermediate language learners were selected from Rasht Islamic Azad University based on convenience sampling. The results of the pretests indicated that participants were homogeneous regarding language proficiency as determined by Babel test, CT by Watson-Glaser critical thinking appraisal (W-GCTA), and writing ability by a writing test. By implementing a quasi-experimental design, the participants were randomly assigned to experimental and control groups. The experimental group received a step-by-step process of teaching CT and utilized CT skills in developing an essay. The control group, in contrast, merely practiced PW. After applying the non-parametric Spearman rank-order correlation, the results revealed that there was a significant correlation between PW and CT (rs =.632, p<.05). The results of the non-parametric Mann-Whitney U test substantiated that there was a significant difference in CT ability of control and experimental groups (U=.000, p<.05), revealing that PW is a vehicle of CT, not an ingredient.